2012
DOI: 10.3233/wor-2012-0474-2405
|View full text |Cite
|
Sign up to set email alerts
|

Swabbing: touchscreen-based input technique for people with hand tremor

Abstract: Interacting with touchscreen computer systems is a challenging task for elderly tremor patients, because of a lower input accuracy caused by their tremor symptoms. Previous observations by Mertens et al. suggested that continuous movements are able to lower these symptoms. In this paper Swabbing, a input method for touchscreen systems based on such motions, is presented. A user study will show that Swabbing is able to reduce the error rate while proving equal user satisfaction compared to standard input techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…MDC represents the number of direction changes within the axis of the detected sub-paths during drag movements. More recently, these measures have been shown successful in differentiating between groups with and without motor impairment Mertens et al, 2012;Montague et al, 2014;Papatheodorou et al, 2019).…”
Section: Data Preparation Maze Performance and Movement Metricsmentioning
confidence: 99%
“…MDC represents the number of direction changes within the axis of the detected sub-paths during drag movements. More recently, these measures have been shown successful in differentiating between groups with and without motor impairment Mertens et al, 2012;Montague et al, 2014;Papatheodorou et al, 2019).…”
Section: Data Preparation Maze Performance and Movement Metricsmentioning
confidence: 99%
“…Nonetheless, interacting with touch screens is challenging for tremor patients due to a lower input accuracy caused by their tremor symptoms. It has been suggested that continuous movements are able to lower these symptoms, but still they may need more attempts to select a target than a healthy subject (Mertens et al, 2012). Additionally, people with motion impairments may find it difficult to keep their finger over the target to select it accurately (Mertens et al, 2012).…”
Section: Desk Researchmentioning
confidence: 99%
“…But high-quality, evidence-based content alone is of limited value, if presented in a way that does not adequately match and address the usability, accessibility, readability (reading with understanding) and health literacy needs of target audiences. An app that is perfectly usable by a younger person might be very difficult to manipulate by an older or disabled person with different and unique usability needs related to ageing and/or physical and cognitive impairment [2,[121][122][123][124][125][126].…”
Section: Ojphimentioning
confidence: 99%